Structure and ecological dominance of mangroves in Tanah Laut, South Kalimantan, Indonesia - P. M. LESTARINA; D. G. BENGEN; T. PRARTONO; M. A. RIFA’I; N. P. ZAMANI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Lestarina PM, Bengen DG, Prartono T, Rifa’I MA, Zamani NP. 2025. Structure and ecological dominance of mangroves in Tanah Laut, South Kalimantan, Indonesia. Biodiversitas 26: 4775-4782. The Tanah Laut Region is one of the districts in South Kalimantan, Indonesia, with significant mangrove potential. However, like many other coastal areas in Indonesia, the mangrove forests in Tanah Laut face serious threats. Strategic development of effective conservation and management requires a comprehensive understanding of the structure of mangrove communities and their ecological conditions. Research on relative density and the Importance Value Index (IVI) provides invaluable quantitative tools for assessing the status of mangrove communities. Relative density provides an overview of a species' abundance relative to others within a community. This study focuses on identifying and characterizing existing mangrove species and evaluating their community structure using quantitative methods. The study was conducted at four selected sampling points in the Tanah Laut coastal area of South Kalimantan: Muara Asam-Asam, Pagatan Besar, and Bawah Layung, Avicennia marina (152.44% to 300 %), and Muara Kintap, Rhizophora mucronata (104.27% to 202.86%) have high importance value indices at nearly all locations. The number of trees found of all types at the research site. The most abundant type of mangrove tree was A. marina with 208 trees, followed by R. mucronata with 155 trees. Bawah Layung site has the highest number of unique species (S = 7) and has a (H?) of 1.670 and a (D) of 0.764. Pagata Besar came second with an H? index of 1.413 and a (D) of 0.688. Muara Kintap and Muara Asam-Asam have only two dominant species,Their H? index values are below 1, and their Simpson's values are below 1. This study revealed that A. marina and R. mucronata species play an important role in maintaining the stability of mangrove ecosystems in the Tanah Laut coastal area. Therefore, to support long-term ecosystem resilience, conservation and rehabilitation efforts should focus on protecting these important species and increasing community heterogeneity.